2009
DOI: 10.1016/j.neubiorev.2008.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress as a risk factor for mental health: Role of neurotrophins from rodents to non-human primates

Abstract: Early adverse events can enhance stress responsiveness and lead to greater susceptibility for psychopathology at adulthood. The epigenetic factors involved in transducing specific features of the rearing environment into stable changes in brain and behavioral plasticity have only begun to be elucidated. Neurotrophic factors, such as Nerve Growth Factor (NGF) and Brain-derived neurotrophic factor (BDNF), are affected by stress and play a major role in brain development and in the trophism of specific neuronal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(142 citation statements)
references
References 164 publications
(266 reference statements)
2
134
0
4
Order By: Relevance
“…Manipulation of mother-pup interactions has been used extensively as a model of early-life stress in rodents with which to study underlying neurobiological mechanisms 7 . One of the most widely used methods involves the separation of the mother from her pups during the first 2 weeks of life, a critical period in the development of nociceptive, sensory, emotional and social functions 4,15,18,39 .…”
Section: Introductionmentioning
confidence: 99%
“…Manipulation of mother-pup interactions has been used extensively as a model of early-life stress in rodents with which to study underlying neurobiological mechanisms 7 . One of the most widely used methods involves the separation of the mother from her pups during the first 2 weeks of life, a critical period in the development of nociceptive, sensory, emotional and social functions 4,15,18,39 .…”
Section: Introductionmentioning
confidence: 99%
“…Hofer's (1987Hofer's ( , 1994 work with rats has shown that multiple systems are regulated by the presence of the mother and quickly become dysregulated when she is physically absent. Even in species less social than ours, physical separation activates painful emotions (Ladd, Owens, & Nemeroff, 1996;Panksepp, 2003;Sanchez et al, 2001) and influences the dynamics of various emotionregulating hormones and neuropeptides (Cirulli, Francia, Berry, Aloe, Alleva, & Suomi 2009). …”
Section: Natural Childbirthmentioning
confidence: 86%
“…The behavior of these infant monkeys were similar to orphaned and hospitalized children separated from their caregiver: the infants appeared depressed-like during separation and the monkeys showed enduring emotional and cognitive problems that continued into adulthood. Research over the past decades has greatly expanded on this research and has identified both immediate and enduring impact of being separated from the mother in nonhuman primates, and extended this work to demonstrate that the quality of maternal care programs neurobehavioral development (Barr et al, 2004;Cirulli et al, 2009;Conti et al, 2012;Coplan et al, 1996;Coplan et al, 1998;Corcoran et al, 2012;Dettling, Feldon, & Pryce, 2002;Harlow & Suomi, 1970;Howell & Sanchez, 2011;Macri, Spinelli, Adriani, Dee Higley, & Laviola, 2007;McCormack, Sanchez, Bardi, & Maestripieri, 2006;Pryce et al, 2005;Rosenblum et al, 1994;Sanchez, 2006;Sanchez, Ladd, & Plotsky, 2001;Stevens, Leckman, Coplan, & Suomi, 2009;Suomi, 1991Suomi, , 2003.…”
Section: Historical Insights: the Importance Of Animal Research To Atmentioning
confidence: 99%
“…The behavior of these infant monkeys were similar to orphaned and hospitalized children separated from their caregiver: the infants appeared depressed-like during separation and the monkeys showed enduring emotional and cognitive problems that continued into adulthood. Research over the past decades has greatly expanded on this research and has identified both immediate and enduring impact of being separated from the mother in nonhuman primates, and extended this work to demonstrate that the quality of maternal care programs neurobehavioral development (Barr et al, 2004;Cirulli et al, 2009;Conti et al, 2012;Coplan et al, 1996;Coplan et al, 1998;Corcoran et al, 2012;Dettling, Feldon, & Pryce, 2002;Harlow & Suomi, 1970;Howell & Sanchez, 2011;Macri, Spinelli, Adriani, Dee Higley, & Laviola, 2007;McCormack, Sanchez, Bardi, & Maestripieri, 2006;Pryce et al, 2005;Rosenblum et al, 1994;Sanchez, 2006;Sanchez, Ladd, & Plotsky, 2001;Stevens, Leckman, Coplan, & Suomi, 2009;Suomi, 1991Suomi, , 2003.The most prolific animal model research on infant neural development has occurred in rodents, which has also provided information on the immediate and enduring effects of early life caregiving, using primarily the model of maternal separation, although there was focus on the effects of sensory stimulation (Denenberg, 1963;Hennessy, Li, & Levine, 1980;Hofer, 1978Hofer, , 1984Hofer, , 1994Levine & Lewis, 1959;McIver, 1965). Convergence of research results across rodents and humans has been reviewed elsewhere and I highlight a few reviews, although many other excellent reviews are available (Branchi & Cirulli, 2014; CadizMoretti, Otero-Garcia, Martinez-Garcia, & Lanuza, 2014;Callaghan & Tottenham, 2016;Chen & Baram, 2016;Daskal...…”
mentioning
confidence: 99%